2010
DOI: 10.1242/jeb.044396
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral modulation of pheromone response by inhibitory host compound in a beetle

Abstract: SUMMARYWe identified several compounds, by gas chromatographic-electroantennographic detection (GC-EAD), that were antennally active in the bark beetle Ips typographus and also abundant in beetle-attacked spruce trees. One of them, 1,8-cineole (Ci), strongly inhibited the attraction to pheromone in the field. Single-sensillum recordings (SSRs) previously showed olfactory receptor neurons (ORNs) on I. typographus antennae selectively responding to Ci. All Ci neurons were found within sensilla co-inhabited by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 59 publications
9
84
0
Order By: Relevance
“…Despite trans-4-thujanol being repellent for bark beetles under laboratory conditions, it remains to be investigated whether it is active in the field. We assume that this compound belongs to the group of already known substances decreasing attraction of I. typographus adults, including 1,8-cineole and (−)-limonene both produced by spruce trees (Andersson et al 2010;Schiebe et al 2012), verbenone released by microorganisms in the galleries of bark beetles (review in Byers 2004) and green leaf volatiles emitted by many non-host trees (Zhang et al 1999), as well as ipsenol and ipsdienol produced by I. typographus males to avoid competition in the later phases of tree attack (Birgersson et al 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite trans-4-thujanol being repellent for bark beetles under laboratory conditions, it remains to be investigated whether it is active in the field. We assume that this compound belongs to the group of already known substances decreasing attraction of I. typographus adults, including 1,8-cineole and (−)-limonene both produced by spruce trees (Andersson et al 2010;Schiebe et al 2012), verbenone released by microorganisms in the galleries of bark beetles (review in Byers 2004) and green leaf volatiles emitted by many non-host trees (Zhang et al 1999), as well as ipsenol and ipsdienol produced by I. typographus males to avoid competition in the later phases of tree attack (Birgersson et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…For I. typographus for example, α-pinene-the predominant monoterpene in Norway spruce-enhances the attractiveness of the aggregation pheromone (Erbilgin et al 2007;Jakuš and Blaženec 2003). Conversely, 1,8-cineole acts as an antagonist inhibiting attraction to the aggregation pheromone (Andersson et al 2010). A field survey indicated that trees that were attacked but not colonised during an outbreak exhibited a greater content of 1,8-cineole than successfully colonised trees (Schiebe et al 2012), suggesting the involvement of this compound in tree resistance.…”
Section: Handling Editor: Aurelien Sallementioning
confidence: 99%
“…Another specific feature of cabbage odor is the high proportion of eucalyptol in its GC-EAD active volatile profile. In bark beetles eucalyptol strongly reduces pheromone attraction, and inhibits the activation of pheromone-OSN, through the activation of a co-localised OSN (Andersson et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A similar story is emerging for aggregation pheromones of tree-killing bark beetles, which during outbreaks can be a serious threat to forests, both planted and unmodified (Raffa et al, 2016). In the European spruce bark beetle, Ips typographus, the herbivore-induced spruce defense compound, 1,8-cineole (Schiebe et al, 2012), strongly reduces attraction to the aggregation pheromone, which is used to coordinate deadly mass-attacks on trees (Andersson et al, 2010;Binyameen et al, 2014). The sensory neuron that detects 1,8-cineole is housed within the same sensilla as that for one of the essential aggregation pheromone components, and when the 1,8-cineole neuron responds, the response to the aggregation pheromone component in the other neuron is inhibited, probably via passive electrical interactions between neurons (Andersson et al, 2010).…”
Section: Targeting Species-specific Receptors Should Be Desirable Fromentioning
confidence: 99%